(untitled) (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2018)
This research deals with the evaluation of buckling behavior for 6061-T4 aluminumalloy under increasing compressive dynamic loads. Two types of columns, long, and theintermediate columns were used. The number of specimens used in the dynamic axialcompression test were 9 samples .(1%) of the length column is the allowable lateraldeflection. For the purpose of calculating the initial deflection, the digital dial gauge wasused and the instrument was set at a distance of (0.7) of length from the fixed condition forthe column. A control system is designed to evaluate the critical buckling and to preventsample failure. The control system consists of a measuring circuit (transmitter circuit) with aflex sensor installed at 0.7 of the total column length of the column's fixed condition. Inaddition, the system contains a shutdown circuit (receiver circuit) to switch off the machineat critical load with a mobile phone for the purpose of displaying deflection data. Theconnection between the transmitter circuit and the receiver wirelessly through the RF sensorand between the transmitter circuit and mobile phone also wirelessly via Bluetooth. Theresults obtained were experimentally compared with the Perry-Robertson formula. It wasfound that the Perry-Robertson formula was a good agreement with the experimental resultswith a safety factor of (1.2) .